(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The complex story of Beirut’s reconstruction after a 15-year civil war is seen as a paradigm for post-war Ukraine. In the recovery of the capital of Lebanon, collaboration between the public and professional sectors played an important role, acting as an alternative or complement to state and commercial private strategies. In contrast to «Solidere» company commercial approach, marked by "architectural amnesia" and the destruction of historical heritage, both public organizations and professional communities of architects and historians advocate for the preservation of cultural heritage as the basis for national reconciliation. The emergence of public movements from the level of direct self-organization of the population was complicated by the specifics of Lebanese society - the stability of ethnoconfessional identity and the corresponding political mobilization after the civil war. The dynamics of interaction allow traditional elites to penetrate civil society and connect the possibilities of its constructive participation in the reconstruction of the city. The dominant "top-down" approaches were focused on the physical aspects of reconstruction, and alternative approaches have also gained some development. However, they were conducted in small settlements, because creating a holistic methodology for Beirut was beyond the current capabilities of progressive research teams, and breakthroughs towards an effective humanitarian approach to post-war reconstruction came too late.